PENGARUH KETERAMPILAN, PENGETAHUAN DAN KOMUNIKASI ANTAR PERSONAL TERHADAP PRODUKTIVITAS KERJA ANGGOTA POLRES BIREUEN - Ramadhan, Ozie; Fauzi, Fauzi (LPPM-UNIKI, 2024)
The article aims to empirically analyze the influence of skills, knowledge and communication on the work productivity of Bireuen Police Personnel members. The research method used is associative with a quantitative approach. Analysis using a path model approach by collecting survey data on a sample of 67 members of Bireuen Police Personnel at the SAMAPTA SAT Unit. The research results show that (1) partially there is an influence of each variable studied, namely skills, knowledge and communication on work productivity of 47.09%, 46.93% and 60.08%. (2) Simultaneously skills, knowledge and communication influence the work productivity of personnel members by 66.0%. (3) There is a causal relationship between the variables of skills and knowledge and communication.